Factors that affect horizontal gene transfer in enteric bacteria - Peterson, Gregory Jay (Kansas State University, 2012)
Antimicrobial resistance (AMR) has arisen as one of the most important public health concerns in the last 60 years. AMR results from pathogenic strains of bacteria adapting to antimicrobial-containing environments through mutations or through horizontal gene transfer (HGT) of genetic material containing resistance genes. Conjugation machinery offers an efficient method for acquisition of AMR and virulence genes, which may be responsible for propelling the evolution of pathogenic bacteria. This dissertation explores the factors, specifically catecholamines and antimicrobials that influence the conjugation frequencies of enteric bacteria including Salmonella, E. coli and Enterococcus. We found that the catecholamine norepinephrine (NE) at physiological concentrations enhanced conjugation efficiencies of a conjugative plasmid from a clinical strain of Salmonella Typhimurium to an E. coli recipient in vitro. Additional experiments determined the influence of the antimicrobial concentrations above, equal to and below the minimum inhibitory concentration (MIC) under in vitro conditions on conjugation efficiencies using an Enterococcus to Enterococcus mating pair in addition to the Salmonella to E. coli mating pair. Conjugation occurred in all concentrations, but efficiencies of transfer were consistently low in 0 MIC and 1 MIC, with increased activity both above and below 1 MIC. These data were fit to a previously described mathematical model and the rate constant E that relates the rate of gene transfer to drug concentration was determined. The data showed highly similar patterns of conjugation efficiencies when compared to the rate constant E. A final study we measured conjugation frequencies when donor Salmonella Typhimurium and the E. coli recipient were exposed to both variable concentrations of oxytetracycline and NE. Conjugation was increased pre- and post- MIC, but conjugation frequencies were not enhanced further by the combination of the oxytetracycline and the NE. This dissertation defines the role of outside factors in conjugative gene transfer, and may provide future insight into better control of AMR.
Keywords: Horizontal gene transfer; Minimum inhibitory concentration; Catecholamines; Bacterial conjugation; Biology (0306); Microbiology (0410); Molecular Biology (0307)